Efficiency in a search and matching model with endogenous participation - James Albrecht; Lucas Navarro; Susan Vroman (Institute for the Study of Labor (IZA), 2009)
We show that in a search/matching model with endogenous participation in which workers are heterogeneous with respect to market productivity, satisfying the Hosios rule leads to excessive vacancy creation. The reason is that the marginal worker does not internalize the effect of his or her participation on average productivity.
urn:nbn:de:101:1-20090403104
Keywords: D8; J6; 330; Search; matching; efficiency; participation; Hosios rule; Arbeitsuche; Suchtheorie; Arbeitsangebot; Arbeitsproduktivität; Offene Stellen; Arbeitsplatzsuchmodell; Theorie